The Role of a Neuropsychologist on a Movement Disorders Deep Brain Stimulation Team. (26th April 2018) - Kubu, Cynthia S
Abstract: The term movement disorders is misleading in the implication that the symptoms are limited to motor problems. Most movement disorders include a variety of neurobehavioral and neurocognitive symptoms that require neuropsychological expertise. The goal of this paper is to provide a rationale and practical roadmap for neuropsychologists' involvement in a Movement Disorders team with a specific focus on pre-operative deep brain stimulation (DBS) evaluations. Pragmatic recommendations regarding requisite skills, clinical practice, recommendations, communication, and benefits are outlined.